2004
DOI: 10.1017/s1355617704103056
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of memory function in community-dwelling elderly: The importance of white matter hyperintensities

Abstract: We sought to identify magnetic resonance-(MR)-imaged structures associated with declarative memory in a community-dwelling sample of elderly Mexican-American individuals with a spectrum of cognitive decline. Measured structures were the hemispheric volumes of the hippocampus (HC), parahippocampal gyrus, and remaining temporal lobes, as well as severity of white matter signal hyperintensities (WMH). Participants were an imaged subsample from the Sacramento Area Latino Study of Aging (SALSA), N 5 122. Individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 57 publications
3
15
1
Order By: Relevance
“…DTI findings had strong associations with AVLT scores, suggesting that WM microstructure alterations may contribute to memory impairment across the patient groups. Our correlation results across the NC and SCD groups support the idea that WM impairment is the strongest structural predictor of delayed recall score, especially in the early stages of AD [38]. Previous studies suggested that the delayed recall test best discriminates early AD and predicts conversion to AD [39, 40].…”
Section: Discussionsupporting
confidence: 82%
“…DTI findings had strong associations with AVLT scores, suggesting that WM microstructure alterations may contribute to memory impairment across the patient groups. Our correlation results across the NC and SCD groups support the idea that WM impairment is the strongest structural predictor of delayed recall score, especially in the early stages of AD [38]. Previous studies suggested that the delayed recall test best discriminates early AD and predicts conversion to AD [39, 40].…”
Section: Discussionsupporting
confidence: 82%
“…This may again point to heterogeneity within this group, with some individuals in the earliest stages of AD and others who are anxious regarding their memory but well. Volume of white matter hyper-intensities has also been found to correlate with cognitive impairment (Petkov et al, 2004). The absence of this finding in our study may be a reflection of our exclusion criteria leading to a group relatively free of white matter disease.…”
Section: Neuroimagingmentioning
confidence: 47%
“…All analyses were performed using gray matter volumes because gray matter volume changes have been found to be predictive of episodic memory performance in dementia patients (Petkov et al, 2004), as opposed to white matter hyperintensities, which were predictive of episodic memory performance only in healthy older adults. However, we also performed the analyses using white matter volumes.…”
Section: Personal Semantic Autobiographical Events and The Effect Omentioning
confidence: 99%